Thermal stability and thermal conductivity of solid electrolytes - Cheng-Wei Wu; Xue Ren; Wu-Xing Zhou; Guofeng Xie; Gang Zhang (APL Materials, 2022)
Compared with liquid organic lithium-ion batteries, solid-state lithium-ion batteries have higher safety performance, so they are expected to become the next generation of energy storage devices and have attracted extensive research attention. The thermal management of the battery is a multi-coupling problem. Battery safety, cycle life, and even electrochemical reactions are all related to it. This Perspective presents the commonly used solid-state electrolytes and recent studies on their thermal stability and thermal transport properties. The thermal decomposition temperature and thermal conductivity are summarized, and we also present the summary and a brief outlook. This Perspective provides a reference for how to design and select high thermal conductive electrolyte materials, which is important for further advancement of solid-state lithium-ion batteries.